TEFTOM: A Promising General Trauma Expectation/Outcome Measure—Results of a Validation Study on Pan-American Ankle and Distal Tibia Trauma Patients. (28th February 2013) - Suk, Michael; Daigl, Monica; Buckley, Richard E.; Paccola, Cleber A. J.; Lorich, Dean G.; Helfet, David L.; Hanson, Beate
Abstract : Background . In orthopedics, there is no instrument specifically designed to assess patients' expectations of their final surgery outcome in general trauma populations. We developed the Trauma Expectation Factor Trauma Outcome Measure (TEFTOM) to investigate the fulfilment of patients' expectations one year after surgery as a measure of general trauma surgical outcomes. The aim of this paper was to assess the psychometric characteristics of this new general trauma outcome measure. Methods . The questionnaire was tested in 201 ankle and distal tibia fracture patients scheduled for surgery. Patients were followed up for twelve months. The TEFTOM questionnaire was evaluated for its criterion validity, internal consistency, reproducibility, and responsiveness. Results . TOM showed good criterion validity against the American Academy of Orthopaedic Surgeons Foot and Ankle Scale (Pearson's correlation coefficient = 0.69–0.77). Internal consistency was acceptable for TEF (Cronbach's alpha = 0.65–0.76) and excellent for TOM (Cronbach's alpha = 0.76–0.85). Reproducibility was moderate to very good (intraclass coefficient correlation (ICC) ≥ 0.67 ) for TEF and very good (ICC ≥ 0.92 ) for TOM. TOM also proved to be responsive to changes in patients' condition over time (Wald test; P < 0.001 ). Conclusions . TEFTOM is a promising tool for measuring general trauma outcomes in terms of patients' expectation fulfilment that proved to be valid, internally consistent, reproducible, and responsive to change.